2000
DOI: 10.4049/jimmunol.165.12.7262
|View full text |Cite
|
Sign up to set email alerts
|

Early Requirement for B Cells for Development of Spontaneous Autoimmune Thyroiditis in NOD.H-2h4 Mice

Abstract: B cells are known to play an important role in the pathogenesis of several autoimmune diseases. NOD.H-2h4 mice develop spontaneous autoimmune thyroiditis (SAT) and anti-mouse thyroglobulin (MTg) autoantibodies, the levels of which correlate closely with the severity of thyroid lesions. NOD.H-2h4 mice genetically deficient in B cells (NOD.Kμnull) or rendered B cell-deficient by treatment from birth with anti-IgM develop minimal SAT. B cells were required some time in the first 4–6 wk after birth, because NOD.Kμ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
126
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 54 publications
(66 reference statements)
8
126
0
Order By: Relevance
“…CD4 ϩ T cells are the primary pathogenic effector cells for SAT and are required for both initiation and maintenance of SAT (1)(2)(3). B cells are required for development of SAT, because B cell-deficient NOD.H-2h4 mice do not develop SAT (7). Our previous studies suggested that B cells were required for activation of pathogenic CD4 ϩ T cells, possibly functioning as important APCs (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CD4 ϩ T cells are the primary pathogenic effector cells for SAT and are required for both initiation and maintenance of SAT (1)(2)(3). B cells are required for development of SAT, because B cell-deficient NOD.H-2h4 mice do not develop SAT (7). Our previous studies suggested that B cells were required for activation of pathogenic CD4 ϩ T cells, possibly functioning as important APCs (7).…”
mentioning
confidence: 99%
“…B cells are required for development of SAT, because B cell-deficient NOD.H-2h4 mice do not develop SAT (7). Our previous studies suggested that B cells were required for activation of pathogenic CD4 ϩ T cells, possibly functioning as important APCs (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In murine autoimmune thyroiditis, Braley-Mullen et al (11) demonstrated the importance of B cells in the initiation of thyroiditis, in an autoantibody-independent manner. In a GD model, Pichurin et al (12) showed that B cell-deficient mice were unable to elicit the normal T cell response to immunization with TSH-R. Conversely, the production of autoantibodies seems dependent on the help of CD4 þ T cells (53).…”
Section: B/t Cell Interaction: the B Cell As An Antigenpresenting Cellmentioning
confidence: 99%
“…In addition to being precursors for antibody-secreting plasma cells, B cells are also efficient antigen-presenting cells (APC) in autoimmune disease, as shown in animal models of diabetes (5), rheumatoid arthritis (RA) (6) and systemic lupus erythematosus (SLE) (7,8). In murine models of autoimmune thyroid disease (AITD), B cells are shown to act as APCs (9,10) and are a prerequisite for the initiation of the disease process (11). Recently, Pichurin et al (12) have demonstrated the importance of B cells on T cell activation in GD.…”
Section: Introductionmentioning
confidence: 99%